Bronchitis and its Treatment Methods: Approaches in Modern Medicine (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Bronchitis is a prevalent respiratory condition marked by inflammation of the bronchial tubes, leading to symptoms such as persistent cough, mucus production, and chest discomfort. While acute bronchitis is typically short-term and viral in origin, chronic bronchitis, often associated with prolonged exposure to irritants such as tobacco smoke and air pollution, requires sustained management and is a key component of chronic obstructive pulmonary disease (COPD). Despite the availability of numerous treatment options, a comprehensive understanding of modern therapeutic approaches integrating both pharmacological and non-pharmacological strategies remains fragmented. This article aims to consolidate current knowledge on the treatment of acute and chronic bronchitis, evaluating conventional methods such as bronchodilators, corticosteroids, antibiotics, and mucolytics, alongside adjunctive approaches including inhalation therapy, pulmonary rehabilitation, lifestyle changes, and preventive vaccinations. The findings confirm that while acute bronchitis can often be managed with symptomatic relief and self-care, chronic bronchitis demands long-term interventions, highlighting the critical roles of smoking cessation, respiratory therapy, and structured rehabilitation programs. A key novelty of this work lies in its integrated review of multidisciplinary management strategies tailored to the type and severity of bronchitis, emphasizing the synergy between medical treatment and lifestyle modification. The implications of these findings support a patient-centered, preventive approach to bronchitis management and suggest avenues for enhancing clinical protocols and public health policies aimed at reducing bronchitis-related morbidity.